2011
DOI: 10.1136/hrt.2010.220509
|View full text |Cite
|
Sign up to set email alerts
|

Variability in on-treatment platelet reactivity explained by CYP2C19*2 genotype is modest in clopidogrel pretreated patients undergoing coronary stenting

Abstract: The CYP2C19*2 loss-of-function polymorphism is associated with a more frequent occurrence of HPR. However, the part of the interindividual variability in on-treatment platelet reactivity explained by CYP2C19*2 genotype is modest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
51
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 13 publications
8
51
0
1
Order By: Relevance
“…However, a study from the Netherlands of 1069 clopidogrel-pretreated patients undergoing elective PCI found that loss-of-function CYP2C19 carrier status explained only part of the variability in platelet reactivity (13.0e20.6%), depending on the test used. 37 One approach to modifying high on-treatment platelet reactivity in carriers of loss-of-function CYP2C19 variants is to use antiplatelet drugs metabolised by different pathways, and this was confirmed by investigators from Korea in a substudy of the CILON-T randomised trial. 38 In patients with loss-of-function CYP2C19 variants who were randomised to dual antiplatelet therapy plus cilostazol, a selective phosphodiesterase-3 inhibitor, on-treatment platelet reactivity was significantly reduced compared with patients who received only aspirin and clopidogrel.…”
Section: Antiplatelet Therapiesdwhat's New?mentioning
confidence: 87%
“…However, a study from the Netherlands of 1069 clopidogrel-pretreated patients undergoing elective PCI found that loss-of-function CYP2C19 carrier status explained only part of the variability in platelet reactivity (13.0e20.6%), depending on the test used. 37 One approach to modifying high on-treatment platelet reactivity in carriers of loss-of-function CYP2C19 variants is to use antiplatelet drugs metabolised by different pathways, and this was confirmed by investigators from Korea in a substudy of the CILON-T randomised trial. 38 In patients with loss-of-function CYP2C19 variants who were randomised to dual antiplatelet therapy plus cilostazol, a selective phosphodiesterase-3 inhibitor, on-treatment platelet reactivity was significantly reduced compared with patients who received only aspirin and clopidogrel.…”
Section: Antiplatelet Therapiesdwhat's New?mentioning
confidence: 87%
“…However, a study from the Netherlands of 1069 clopidogrel-pretreated patients undergoing elective PCI found that loss-of-function CYP2C19 carrier status explained only part of the variability in platelet reactivity (13.0-20.6%), depending on the test used. 37 One approach to modifying high on-treatment platelet reactivity in carriers of loss-of-function CYP2C19 variants is to use antiplatelet drugs metabolised by different pathways, and this was confirmed by investigators from Korea in a substudy of the CILON-T randomised trial. 38 In patients with loss-of-function CYP2C19 vari ants who were randomised to dual antiplatelet therapy plus cilostazol, a selective phosphodiesterase-3 inhibitor, on-treatment platelet reactivity was significantly reduced compared with patients who received only aspirin and clopidogrel.…”
Section: Antiplatelet Therapies-what's New?mentioning
confidence: 87%
“…In the POPULAR study, CYP2C19*2 genotype was associated with approximately 4-6% and clinical variables with 9-17% variability in on-treatment platelet reactivity as assessed by ADP-induced platelet aggregation and VerifyNow P2Y12 assay. In the latter study both CYP2C19*2 and clinical variables were together associated with 13-21% on-treatment platelet reactivity [37].…”
Section: Influence Of Cyp2c19 Polymorphisms On Clopidogrel Metabolismmentioning
confidence: 94%